2007
DOI: 10.1242/jcs.03371
|View full text |Cite
|
Sign up to set email alerts
|

IL-13 mediates the recruitment of reserve cells for fusion during IGF-1-induced hypertrophy of human myotubes

Abstract: Insulin-like growth factor-1 (IGF-1) has been shown to induce skeletal muscle hypertrophy, to prevent the loss of muscle mass with ageing and to improve the muscle phenotype of dystrophic mice. We previously developed a model of IGF-1-induced hypertrophy of human myotubes, in which hypertrophy was not only characterized by an increase in myotube size and myosin content but also by an increased recruitment of reserve cells for fusion. Here, we describe a new mechanism of IGF-1-induced hypertrophy by demonstrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 78 publications
(114 reference statements)
4
52
0
Order By: Relevance
“…In human myoblast, it was shown that interleukin 13 (IL-13) had positive effect on myoblast fusion as it stimulates the recruitment of reserve cells to increase myotube size (Jacquemin et al, 2007). We first confirmed that exogenous IL-13 increased dosedependently the number of nuclei per myotube (Fig.…”
Section: Trpc Interleukin 13 and Myoblast Fusionsupporting
confidence: 58%
See 1 more Smart Citation
“…In human myoblast, it was shown that interleukin 13 (IL-13) had positive effect on myoblast fusion as it stimulates the recruitment of reserve cells to increase myotube size (Jacquemin et al, 2007). We first confirmed that exogenous IL-13 increased dosedependently the number of nuclei per myotube (Fig.…”
Section: Trpc Interleukin 13 and Myoblast Fusionsupporting
confidence: 58%
“…The role of IL-4 in the fusion of myoblasts to nascent myotubes was confirmed in human, and further extended to a role of promoting myoblast migration (Lafreniere et al, 2006). Using a model of IGF-1-mediated human myotube hypertrophy, the group of Mouly showed that IL-13, but not IL-4, favors reserve cells activation, and their subsequent recruitment and fusion to myotubes (Jacquemin et al, 2007). An in vivo study further pointed to a role of IL-4 and IL-13 in exercise-induced human muscle hypertrophy (Prokopchuk et al, 2007).…”
Section: /Trpc4mentioning
confidence: 92%
“…In muscle, IGF-I Ea is a potent growth factor that stimulates both the rate of mRNA transcription of contractile proteins (53) and their rate of translation via phosphatidylinositol-3 kinase/ Akt/mTOR pathway (32). The splice variant of IGF-I, MGF, seems to be involved in satellite cell activation and migration of myoblasts and satellite cells, resulting in an increased myonuclear density in the muscle fiber (44,65).…”
Section: E391 Muscle Anabolic and Metabolic Factors In Osteocytesmentioning
confidence: 99%
“…Besides Akt, IGF-1 acts on the mTOR/p70S6K and GSK-3 pathways, both of which are involved in the control of protein translocation. IGF-1 also potentiates the recruitment of reserve cells for fusion via the secretion of IL-13 by myotubes under the control of NFATc2 [16].…”
Section: Introductionmentioning
confidence: 99%